Experimental and Numerical Investigation of Cutting Forces and Temperatures in Milling of Custom 450 Steel - Gökçe, Harun (Archives of Metallurgy and Materials, 2022)
Stainless steels have a wide usage field, their needs as structural parts are increasing day by day due to their resistance to corrosion and providing sufficient mechanical strength in environments that would cause corrosion. In addition to high mechanical properties of the stainless steels, the low heat transmission coefficients bring problems during machining. In this study, the suitable cutting tool and cutting parameters have been evaluated in terms of cutting forces and the tool temperature, the experimental results and finite element analysis have been compared in the milling of Custom 450 stainless steel which offers especially an excellent working opportunity at high temperature and salinity environment. Milling experiments have been carried out using L16 experimental design for Taguchi method. Four simulations have been made using finite element method with corresponding values in L16 orthogonal array for optimum cutting tool and the results were compared in terms of cutting forces and tool temperature changes.
Keywords: End milling; Finite element method; Custom 450; cutting forces; Cutting temperature